Revisiting the history of Takayasu's disease studies and surgical techniques used in its treatment - A. E. Zotikov; V. A. Kulbak; A. V. Abrosimov; D. A. Lavrentyev («REMEDIUM GROUP» Ltd., 2020)
Nonspecific aortoarteritis is a systemic disease, which has been referred to the group of vasculitis affecting elastic and muscular arteries oflarge and medium calibre with the inflammatory processlocalized in the media and adventitia. The article presents the history of development of ideas about clinical manifestations, morphological changes and the course of the disease from 1761 to the present day, the timeline of medical advances in this disease studies. The genuine interest in nonspecific aortoarteritis arose at the beginning of thelast century, when the Japanese ophthalmologist Mikito Takayasu reported unusual changes in the retinal vessels of a 21-year-old Japanese girl suffering from recurrent bouts of syncope. The first publications dealt with clinical manifestations in the patients, who had only brachiocephalic arterial involvement. In the early 60s, it was found that nonspecific aortoarteritis (Takayasu's disease) can affect not only the branches of the aortic arch, but also the thoracic aorta, renal and visceral arteries. It was the mosaic clinical manifestations in patients with various forms of Takayasu's disease that caused the presentation of the disease in theliterature until the mid-1970s under various terms such as "pulseless disease", "arteritis of young women", "brachiocephalic arteritis", "atypical coarctation of aorta", "Martorell's syndrome", "syndrome of obliteration of the supra-aortic trunks", "panaortitis" or "panarteritis", "aortitis syndrome", "mid-aortic syndrome", "occlusive thromboarteriopathy". The review details the epidemiology and prevalence of this disease. Views not only on the etiology and pathogenesis, but also on the methods of treating this disease have changed since M. Takayasu's publication in 1908. Much attention is paid to the historical aspect of the first surgical procedures. Starting in 1951, the surgical method has firmly taken the lead in the treatment of stenosis of the carotid arteries, thoracic aorta, renal and visceral arteries. Surgical concepts changed, but the literature data indicate the sustainability of the basic principle of treatment: combination of surgical interventions and various antiinflammatory therapy regimens.